Chillida in America. An encounter with modernity on the other side of the Atlantic - López-Martín, Pablo (Cuadernos de Proyectos Arquitectónicos, 2023)
In 1958 Eduardo Chillida received a scholarship from the Graham Foundation of Chicago in which he was encouraged to explore deeper into those aspects of his work that are closest to the architectural discipline. Behind this scholarship there were essential figures for the dissemination of the values of modern architecture in America such as Mies van der Rohe, Sigfreid Giedion or Josep Lluis Sert. Chillida’s work shows a step from the Ikaraundi, which began in 1957, to the works that are decidedly interested in spatial phenomena (the Praise of Architecture or the Meeting Places) at the end of the 60s. This year of scholarship of hinge and approach to the field of architecture as he himself recognizes in the report that he will write for its reception. This chapter of his biography has until now barely been considered to explain this momentous turn in his career.